2020
DOI: 10.1371/journal.ppat.1008421
|View full text |Cite|
|
Sign up to set email alerts
|

Are pangolins the intermediate host of the 2019 novel coronavirus (SARS-CoV-2)?

Abstract: The outbreak of a novel corona Virus Disease 2019 in the city of Wuhan, China has resulted in more than 1.7 million laboratory confirmed cases all over the world. Recent studies showed that SARS-CoV-2 was likely originated from bats, but its intermediate hosts are still largely unknown. In this study, we assembled the complete genome of a coronavirus identified in 3 sick Malayan pangolins. The molecular and phylogenetic analyses showed that this pangolin coronavirus (pangolin-CoV-2020) is genetically related … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
394
2
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 360 publications
(438 citation statements)
references
References 31 publications
27
394
2
9
Order By: Relevance
“…A newly reported bat RmYN02 shares 93.3% nucleotide identity with SARS-CoV-2 genomewide and 97.2% identity in the 1ab gene (Zhou et al, 2020a). Besides bat CoVs, pangolin/GD/2019 CoV and pangolin/GX/P5L/2017 CoV share up to 90% and 85.2% sequence identity with SARS-CoV-2, respectively (Liu et al, 2020;Zhang et al, 2020). While the origin of the novel coronavirus appears to be in bat reservoirs, there is still no definitive evidence of an intermediate host that could have transmitted the virus to humans.…”
Section: Introductionmentioning
confidence: 97%
“…A newly reported bat RmYN02 shares 93.3% nucleotide identity with SARS-CoV-2 genomewide and 97.2% identity in the 1ab gene (Zhou et al, 2020a). Besides bat CoVs, pangolin/GD/2019 CoV and pangolin/GX/P5L/2017 CoV share up to 90% and 85.2% sequence identity with SARS-CoV-2, respectively (Liu et al, 2020;Zhang et al, 2020). While the origin of the novel coronavirus appears to be in bat reservoirs, there is still no definitive evidence of an intermediate host that could have transmitted the virus to humans.…”
Section: Introductionmentioning
confidence: 97%
“…Pangolins were suggested to be involved in the species jump of SARS-CoV-2 to humans (37,42). However, more recent studies have disputed this notion (37,43,44). Finally, while the links among Hominidae, Mustelidae (minks), and Felidae (tigers) were deduced, it remains to be seen how SARS-CoV-2 viruses were transmitted among them.…”
Section: Resultsmentioning
confidence: 99%
“…It found that the novel coronavirus appears to be far more adapted to human ACE2 receptors than those found in bats, which is unexpected given that bats are the virus's assumed source, and which lead the lead research to observe that SARS-CoV-2 was perfectly adapted to infect humans since its first contact with us, and had no apparent need to for any adaptive evolution at all. [46] Although the novel coronavirus also appears to have a high affinity for the pangolin ACE2 receptor, [47] phylogenetic analysis of the neutral sites that best determine shared heritage [48] and a distinctive amino acid sequence both indicate that pangolins are unlikely to have served as an intermediate host, [47] so this affinity is likely due to the convergent motifs that often mark viral evolution and not shared heritage. The unexpected immediate www.advancedsciencenews.com www.bioessays-journal.com affinity for humans was also reflected by another preprint, which observed that SARS-CoV-2 appeared just as adapted to humans at the very start of its epidemic as SARS-CoV was in the latest stages of its emergence, [49] an unexpected finding since viruses are expected to mutate substantially as they acclimate to a new species.…”
Section: Ferreting Out the Signs Of Serial Passagementioning
confidence: 99%